Variation of Circulating Inflammatory Mediators in Staphylococcus aureus and Escherichia coli Bloodstream Infection - Duan, Jinyan (Med Sci Monit, 2016)
BACKGROUND: The aim of this study was to examine the behavior of circulating inflammatory mediators and to exclude gram-positive from gram-negative bloodstream infections. Results may be helpful in selection of optimal specific antibiotic therapies. MATERIAL/METHODS: Mice (25–27 g) were randomized to 3 groups infected with Staphylococcus aureus (S. aureus) ATCC 25923, Escherichia coli (E. coli) ATCC 25922, or phosphate-buffered saline (PBS). The white blood cell count (WBC) and the concentrations of serum C-reactive protein (CRP), procalcitonin (PCT), interleukin (IL)-1α, IL-1β, IL-6, IL-10, monocyte chemotactic protein-1 (MCP-1), and macrophage inflammatory protein-1α (MIP-1α) were detected in blood samples at different time intervals after intravenous tail injection. RESULTS: The results showed that compared to the control mice, infected animals exhibited significantly higher levels of all mediators after bacterial infection. Moreover, compared to the mice that received S. aureus, animals with E. coli infection showed significantly greater increases in serum IL-1α, IL-1β, IL-6, MCP-1, and MIP-1α levels. CONCLUSIONS: These results suggest that the use of the analyzed serum markers at an early stage of bloodstream infection may give useful information for the clinician to distinguish gram-negative from gram-positive infections.